ACTIVITY MONITORING OF A NTIBODIES TO HIV-1 STRUCTURAL PROTEINS IN A BSENCE OF ANTIRETROVIRAL TREATMENT AND IN THE COURSE OF THERAPY - G. A. Ryasanova; I. M. Fazulzyanova (Медицинская иммунология)
Abstract. In HIV-infected patients, the process of antibody production to certain HIV-I structural proteins proceeds in differential manner, depending on the antigen localization. Upon progression of the disease, an increased ratio of antibodies to env surface glycoproteins is found, along with decreased percentage of antibodies to gag gene proteins.